Islamic Education Leadership Bibliometric Trends and Collaboration Networks: Tren Bibliometrik Kepemimpinan Pendidikan Islam dan Jaringan Kolaborasi - Sukardi, Sukardi; Lismawati, Lismawati (Halaqa: Islamic Education Journal, 2026)
Despite the rising significance of Islamic Education Leadership, no extensive bibliometric study has been done to investigate its correlation with educational innovation and religious moderation. With the help of Biblioshiny (RStudio) and VOSviewer, this study presents a map of publication trends, topic clusters, and cooperation networks for 280 Scopus-indexed papers published between 2010 and 2025. Main findings: (1) This field becoming more visible as publications rose to 68 in 2025. (2) Holistic, value-based and gender-sensitive management and organizational structures so that spiritual leadership, women’s leadership and maqasid syariah | are the three significant development problems. (3) Indonesia generates the most articles (155) and is the center of international cooperation (betweenness: 15,000; pagerank: 0.330), but the intra-author network disintegrates clearly. This is the first bibliometric study that connects Islamic Educational Leadership and pedagogical innovation to religious moderation. Examples of utilization for Islamic schools are evidence-based curriculum reform, inclusive leadership development and cross-institutional research cooperation. Highlights• Publication growth demonstrates rapid expansion of the research field after 2019• Thematic clusters emphasize value-oriented, gender-inclusive, and spiritual leadership paradigms• Global collaboration is centralized in Indonesia with fragmented author-level networks Keyword  Islamic Education Leadership, Bibliometric Analysis, Religious Moderation, Pedagogical Innovation, Collaboration Network